How do coaches operationalise long-term technical training in elite golf? - Orr, S.; Carson, H. J.; Cruickshank, A. (International Sport Coaching Journal, 2022)
Long-term training is a common approach within the applied setting for components of physiology and strength and conditioning, for example. However, less is known about the reality of training across similar timescales from a technical perspective. Taking the highly technical sport of golf, current research rarely considers coaching technique beyond a single session or with the aim to understand the reality for, or challenges faced by, coaches working at the elite level. Accordingly, this qualitative study explored the goals, structure, and methods of coaches` long-term technical work with players at macro-, meso-, and microlevels. Findings revealed that (a) coaches attempted to undertake technical refinement with players but without a clear systematic process, (b) there is little coherence and consistency across the levels of work, (c) the process and timescales of technical work are considered unpredictable and uncertain, and (d) long-term planning is seen as subservient to meeting players` immediate performance needs. These results highlight the complexity of long-term technical work at the elite level and the need for coaches to develop both a sound and clear rationale through a more comprehensive case conceptualisation process, as well as a greater alignment to the scientific literature, to advance future practice.